Grassland restoration impacts human-wildlife and social conflicts in the Chyulu Hills, Kenya - Donatti, Camila I.; Moraga-Lewy, Nora; Nyongesa, Josephat; Mwanzia, Maureen; Edmond, Janet; Fedele, Giacomo (Frontiers in Environmental Science, 2025)
African grasslands provide benefits for human communities but are negatively impacted by climate change. Climate impacts, combined with human population growth, can increase competition and conflict among humans and wildlife. Grassland restoration, a type of Nature-based Solution for climate adaptation, can improve farmers’ livelihoods by increasing the availability of water and pasture for livestock during drought events. Grassland restoration can also potentially help farmers adapt to climate change by providing human security benefits through a reduction in conflicts, which can also reduce consequent retaliatory measures on wildlife. However, those connections have not been widely explored. This paper assesses whether grassland restoration can reduce human-wildlife and social conflicts in Kenya. We collected information on conflicts using household surveys implemented over 16 months in a total of 1,567 households in Chyulu Hills when grassland restoration was also implemented. Results showed that 88.9% of the households interviewed experienced human-wildlife conflicts and 32% experienced social conflicts. There was a negative and significant correlation between the area restored in each site and both the number of human-wildlife conflicts and the number of social conflicts, showing that conflicts decrease as restoration increases. We also used time as a proxy for restoration, as areas restored and restoration activities increased through time. We did not find a decrease in human-wildlife conflicts over time, but we did find an overall decrease in social conflicts over time, as well as a reduction in the feeling of insecurity. However, not all households behave in the same way. Households led by women experienced a higher number of social conflicts compared to households led by men. Likewise, a higher number of households led by women had a perception of insecurity compared to households led by men. The results of this study provides recommendations for future projects, stakeholders, policy and decisions makers: a) to continue tracking conflicts in Chyulu Hills to understand the connections between grassland restoration and conflicts in the long-term, b) to identify and scale-up measures to mitigate human-wildlife conflicts considering the multiple conflict-causing species, including humans, and c) to consider the needs, perceptions and interests of women in designing strategies to mitigate conflicts.